Juridical Study On Regulation Of Buying And Selling Trading Robot In Indonesia's Positive Law - Ni Made Trisna Dewi (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2022)
The use of trading robots in foreign currency trading commonly known as 'forex trading' has generated a tumultuous polemic. However, in its development, although the Civil Code regulates buying and selling, there are no clear rules governing the buying and selling of trading robots, there is a vagueness in the norms of regulation related to trading robots so it is important to research and discuss so as not to cause losses in the future. Based on the background of the problems described above, the authors formulate the following problems: How is the legal regulation of buying and selling trading robots in Indonesian positive law? What are the legal consequences of buying and selling trading robots? The research method used in this research is the type of normative legal research (normative law research) where normative legal research is legal research conducted by examining library materials or secondary data. using normative case studies. The conclusion in this study is the legal regulations for buying and selling trading robots have not yet been clearly regulated in a specific regulation by the authorized institutions, namely Bappebti and Bapepam, where the current buying and selling is still using The Civil Code (KUHPer) as the basis for buying and selling trading robots. The legal consequences of buying and selling trading robots today are based on the Civil Code (KUHPer), where trading robot trading violates Article 1320 of the Civil Code (KUHPer), so it is canceled or null and void.